Uma abordagem com uso de M-Learning na aprendizagem de cálculo diferencial e integral em cursos de engenharia baseada em ABP e modelagem matemática - Prevot, Fulvio Bianco (2019)
Research indicates that most of engineering students in Brazil do not perform well in Differential and Integral Calculus (ICD) courses, due to some factors, such as precarious mathematical basis, brought from previous steps of formal education, as well as ICD contents present relative degree of abstraction. In Higher Education Institutions, even providing some kind of accompaniment strategies and assistance to Students (e.g., solving doubt shifts, monitoring), those, showing greater learning roblems, still seem to present many difficulties. Smartphones are widely used by students, especially in social networks, which is very important, when thinking of using mobile devices to support learning, inside or outside classes. Many available math apps are free, which does not incur in additional charges for students. This work proposes a methodological approach to ICD teaching and learning, grounded on Problem-Based Learning and Mathematical Modeling, involving m-learning (based on Activity Theory) and in the use of mathematical apps to solve actual Engineering problems. The research methodology was a case study of application of the proposed methodological approach, in a group of 61 students of engineering courses. Qualitative Analysis Results of data pointed to approval of the methodology by most students, as well as to higher levels of motivation and interest in learning and applying ICD techniques. In addition, this research showed a positive impact in using m-learning resources, mobile devices and mathematical software.